Gender differences among patients with primary ankylosing spondylitis and spondylitis associated with psoriasis and inflammatory bowel disease in an iberoamerican spondyloarthritis cohort. Issue 51 (December 2016) - Landi, Margarita; Maldonado-Ficco, Hernán; Perez-Alamino, Rodolfo; Maldonado-Cocco, José A.; Citera, Gustavo; Arturi, Pablo; Sampaio-Barros, Percival D.; Flores Alvarado, Diana E.; Burgos-Vargas, Rubén; Santos, Elena; Palleiro, Daniel; Gutiérrez, Miguel A.; et al.
Abstract : Abstract: The aim of the study was to compare clinical manifestations, disease activity, functional capacity, spinal mobility, and radiological findings between men and women from a multicenter, multiethnic Ibero-American cohort of patients with Spondyloarthritis (SpA). This observational cross-section study included 1264 consecutive SpA patients who fulfilled the modified New York criteria for ankylosing spondylitis (AS). Demographic, clinical, and radiologic data were evaluated. Categorical data were compared by X 2 or Fisher's exact tests and continuous variables by ANOVA with post-hoc tests. Primary AS was diagnosed in 1072 patients, psoriatic spondylitis in 147, and spondylitis associated to inflammatory bowel disease (IBD) in 45 patients. Overall, male patients were significantly younger, had longer diagnostic delay, lower disease activity, worse spinal mobility, better quality of life, and more severe radiologic damage. Dactylitis and enthesitis, as well as swollen joint count, were significantly more common among women. In primary AS, there was a marked male predominance (76.2%). Among patients with psoriatic spondylitis, male predominance was lower (57.8%), but was also associated with worse spinal mobility and more severe radiologic damage. In the total population, male patients with primary AS referred higher permanent work disability (13.2% vs 6.9%; P  < 0.05), although no difference was observed in psoriatic or IBD spondylitis according to the gender. Among Ibero-American SpA patients, there are some differences in clinical and radiological manifestations, men showing more structural damage, whereas women more active disease. These data suggest that the phenotype of SpA differs between genders. This can influence the subsequent diagnostic approach and therapeutic decisions.